Concentrations of ammoniac nitrogen, nitrite and nitrate in areas of oyster culture in Cananeia-SP, Brazil - Edison Barbieri; Helcio Luis de Almeida Marques; Ana Cristina Vigliar Bondioli; Marcos Buhrer Campolim; Alessandra Tegon Ferrarini (O Mundo da Saúde)
Nitrogen plays a key role in aquatic systems, especially in environments which are influenced both by marine and freshwater, such as estuaries. The aim of this study was to evaluate aspects of water quality of Crassostrea spp. aquaculture sites in Cananeia (SP, Brazil) and adequacy thereof for the cultivation of mollusks in relation to concentrations of total ammoniacal nitrogen, nitrite and nitrate. Variations in concentrations of total ammoniacal nitrogen were 0.8 to 3.2 μmol/L, nitrite 0.1 to 3.2 μmol/L, and nitrate from 0.1 to 1.9 μmol/L. Analyzing these data in all seasons together, we found that average total ammoniacal nitrogen and nitrite levels were significantly different for the tides and neap tide. These concentrations recorded at Cananeia are similar to those observed for other estuarine tropical and subtropical regions of the world.